Ergonomic posture assessment approaches for new welder: a study in technical Institution - Syazwani Mohd Fadzil; Mohd Yusof Md Daud; Khairul Fahzan Salleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Welding practical work is a compulsory learning process for all mechanical engineering students in Malaysian polytechnics, students will spend 2 to 4 hours a week doing practical work. Because of that, this situation can cause problems for students when performing tasks, including body posture and manual handling during practical work which can result in musculoskeletal disorders (MSD), in addition non-standard instructions for performing tasks also happen. This study aims to identify the risk of postural problems during welding practical work and suggest an appropriate ergonomic posture assessment to reduce the risk of MSD. In order to assess the position of body posture during welding practical work at technical education institutions, the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) tools were used to observe body posture during practical work and specifically to see the bending level of body parts during work welding practice. Analysis and evaluation were carried out using REBA and RULA and found that the final score for RULA was at a value of 7 and the score for REBA was 9 in the same welding practical. Based on these two scores it was found that welders are at high risk to getting cumulative trauma disorder (CTD) which can also result in MSD. In conclusion, both REBA and RULA body posture assessment tools can be used to assess body posture when carrying out practical work, however, REBA is more suitable because there is an assessment of the leg part which usually involves the leg part while welding, either standing, sitting or squatting. (CTD).